Os benefícios do Reiki em mulheres adultas e idosas com dor crônica associada a transtornos de ansiedade e depressão - Moraes, Isabela Firmino de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Introduction: Reiki is considered an energy rebalancing system that acts directly on the cause of health problems. It was included in the National Policy on Integrative and Complementary Practices (PNPIC in Portuguese), in 2017. Studies show that 37% of Brazilians suffer from chronic pain, most of them women. Chronic pain may be accompanied by anxiety, depression, and adverse effects from prolonged use of medications. Reiki is an inexpensive and easy to apply therapy. Greater exploitation is considered relevant over its possible effects to the Unified Health System (SUS in Portuguese) users, affected by chronic pain, anxiety, depression or other conditions. Objective: Understanding the effects of Reiki in female patients, adult and elderly with chronic pain associated with anxiety and depression disorders. Methods: As a methodological reference, qualitative methodology was adopted using thematic content analysis by the Bardin method.The research was carried out in a Basic Health Unit in Botucatu-SP. A group of 25 participants [female gender, age > 40, pain for period ≥ 3 months, score of possible or probable depression/anxiety in the Hospital Anxiety and Depression Scale (HAD)] was randomized into two groups: Reiki group (RG) and control group (CG), which were developed in eight sessions once a week with duration of 20 minutes each. In both groups the participants sat on the chairs, in silence and blindfolded; with a volunteer behind each one of them, who in RG, ministered Reiki towards “heart chakra” on the backs of the participants; and in CG, the volunteers remained seated on the chair without any acting. After the eight sessions, RG participants attended a focal group or an individual semi-structured interview, where they exposed the subjective aspects experienced, under a posterior analysis. Results and discussion: From the participants' reports, four thematic categories emerged: I) The effect of Reiki on pain - physical and psychoemotional repercussions during and after Reiki sessions; II) Reiki and the impact on daily life; III) Subjective image on Reiki and Spirituality; IV) Considerations about the lived experience - Reiki in the community. It was reported: improvement of pain (except for one participant), relaxation, feelings of Peace, lightness, behavioral change and interest in more knowledge about Reiki. Final considerations: The results have been shown to be promising regarding the benefits of Reiki in women with chronic pain associated with anxiety and depression disorders. It was noted the need for new quali and quantitative researches designed to better investigate Reiki and other Integrative and Complementary Practices (PIC in Portuguese), exploring their potentialities in the SUS. KEYWORDS

Introdução: O Reiki é considerado um sistema de reequilíbrio energético que atua na causa dos problemas de saúde. Foi incluído à Política Nacional de Práticas Integrativas e Complementares (PNPIC), em 2017. Estudos apontam que 37% dos brasileiros sofrem de dor crônica, sendo a maioria mulheres. A dor crônica pode ser acompanhada pela ansiedade, depressão e os efeitos adversos pelo uso prolongado de medicamentos. O Reiki é uma terapia de baixo custo e fácil aplicação. Considera-se relevante maior exploração sobre seus possíveis efeitos a usuários do Sistema Único de Saúde (SUS) acometidos pela dor crônica, ansiedade, depressão ou outras condições. Objetivo: Compreender os efeitos do Reiki em pacientes do sexo feminino, adultas e idosas com dor crônica associada a transtornos de ansiedade e depressão. Métodos: Como referencial metodológico foi adotada metodologia qualitativa utilizando análise de conteúdo temático pelo método Bardin. A pesquisa foi realizada em uma Unidade Básica de Saúde em Botucatu-SP. Um grupo de 25 participantes [sexo feminino, idade >40, dor por período ≥ 3 meses, score de possível ou provável depressão/ansiedade pela Escala Hospitalar de Ansiedade e Depressão (HAD)] foi dividido por sorteio entre: grupo Reiki (GR) e grupo controle (GC), que desenvolveram-se em oito sessões semanais com duração de 20 minutos. Nos grupos, as participantes permaneceram sentadas em cadeiras, em silêncio e com olhos vendados; tendo atrás de cada uma, um voluntário. No GR os voluntários ministraram Reiki em direção ao “chakra cardíaco”, nas costas das participantes; e no GC, os voluntários permaneceram sentados sem qualquer atuação. Após as oito sessões, as participantes do GR compareceram a um grupo focal ou entrevista semiestruturada individual onde expuseram os aspectos subjetivos vivenciados, sob posterior análise. Resultados e discussão: A partir dos relatos das participantes, emergiram quatro categorias temáticas: I) Efeito do Reiki na dor - repercussões físicas e psicoemocionais durante e após sessões de Reiki; II) Reiki e o impacto na vida diária; III) Imagem subjetiva sobre o Reiki e a Espiritualidade; IV) Considerações sobre a experiência vivida – o Reiki na comunidade. Foram reportados: melhora da dor (exceto a uma participante), relaxamento, sensações de paz, leveza, mudança comportamental e interesse por maiores conhecimentos sobre o Reiki. Considerações finais: Os resultados demonstraram-se promissores em relação aos benefícios do Reiki em mulheres com dor crônica associada a transtornos de ansiedade e depressão. Notou-se a necessidade de novas pesquisas, quali e quantitativas bem delineadas para melhor investigação do Reiki e demais Práticas Integrativas e Complementares (PIC), explorando suas potencialidades no SUS.
Benefits of Reiki in adult and elderly women with chronic pain associated with anxiety and depression disorders
Keywords: Reiki (Chronic pain); Women; Anxiety; Depression; Reiki (Sistema de cura).; Dor intratavel; Ansiedade nas mulheres; Depressão